Regulation of Pain Genes—Capsaicin vs Resiniferatoxin: Reassessment of Transcriptomic Data - Singla, Rajeev K.; Sultana, Adiba; Alam, Md. Shahin; Shen, Bairong (Frontiers in Pharmacology, 2020)
Emerging evidences have showed strong association between neuropathic pain and chronic diseases. In recent years, more and more attention has been attracted on the treatment of neuropathic pain. Natural products, such as capsaicin and resiniferatoxin, have been well utilized to treat this disease. In this study, we aim to compare the regulatory effects of capsaicin and resiniferatoxin on the pain related genes. Public transcriptomic and microarray data were obtained from GEO DataSets and then analyzed. Differentially expressed genes were selected for further functional analysis, including pathway enrichment, protein-protein interaction and regulatory network analysis. Pain associated genes were extracted with the reference of two pain gene databases and the effects of these two natural drugs on the pain associated genes were measured. The results of our research indicate that as compared to capsaicin, resiniferatoxin regulates more non-pain associated genes as well as it has more negative impact on the beneficial genes which are supposed to alleviate nociception and hypersensitivity by themselves.